Maternal Moderate Physical Training during Pregnancy Attenuates the Effects of a Low-Protein Diet on the Impaired Secretion of Insulin in Rats: Potential Role for Compensation of Insulin Resistance and Preventing Gestational Diabetes Mellitus - Leandro, Carol Góis (Hindawi Publishing Corporation, 2012)
The effects of pregestational and gestational low-to-moderate physical training on insulin secretion in undernourished mothers were evaluated. Virgin female Wistar rats were divided into four groups as follows: control (C, n = 5); trained (T, n = 5); low-protein diet (LP, n = 5); trained with a low-protein diet (T + LP, n = 5). Trained rats ran on a treadmill over a period of 4 weeks before mate (5 days week(−1) and 60 min day(−1), at 65% of VO(2max)). At pregnancy, the intensity and duration of the exercise were reduced. Low-protein groups were provided with an 8% casein diet, and controls were provided with a 17% casein diet. At third day after delivery, mothers and pups were killed and islets were isolated by collagenase digestion of pancreas and incubated for a further 1 h with medium containing 5.6 or 16.7 mM glucose. T mothers showed increased insulin secretion by isolated islets incubated with 16.7 mM glucose, whereas LP group showed reduced secretion of insulin by isolated islets when compared with both C and LP + T groups. Physical training before and during pregnancy attenuated the effects of a low-protein diet on the secretion of insulin, suggesting a potential role for compensation of insulin resistance and preventing gestational diabetes mellitus.